RELEVANCE OF THE AGRICULTURAL SECTOR AS AN INCOME GENERATOR IN THE STATES WITH THE HIGHEST POVERTY RATES IN MEXICO - Andrés Aurelio López Santiago; Rafael García Vázquez; Francisco Pérez Soto; Juan Hernández Ortiz; Marco Andrés López Santiago; Blanca Isabel Sánchez Toledano (Journal of Animal and Plant Sciences, 2024)
Mexico has undergone a transition from a predominantly agricultural society to one that is more diverse in terms of sources of income. Nevertheless, it has not been fully analyzed how this transition has affected the welfare of families and their members. Therefore, the objective of the study was to analyze the effect of each source of income on the welfare of family units experiencing conditions of poverty in Mexico. The states analyzed were those with the highest poverty rates, such as: Campeche, Chiapas, Guerrero, Oaxaca, Puebla, and Veracruz. An econometric model was used, and based on the results, elasticities were calculated to determine the impact of each income on welfare in percentage terms. To generate the model, data from the National Survey of Household Income and Expenditure were used. The sum of the expenses in the food and non-food baskets was considered as the dependent variable, while the income was taken as the independent variable. The results indicated that the income from subordinate work is the one that makes up the largest contribution, with an increase of 0.346%, followed by transfers, which presented an increase of 0.107%. On the other hand, remittances had a better growth compared to agricultural and livestock income, with an increase of 0.008%. The current situation that shows a decrease in the relevance of the agricultural sector as a generator of welfare is reaffirmed, which has led to a high dependence on government transfers.
Keywords: welfare; income; econometric model; elasticities; remittance